(untitled) (ModaPalavra e-periódico, 2019)
The French edition of the Vogue published in February 2006, entirely devoted to Argentina, including the fashion editorial Tango des Passions, symbolically revealed the approximation of cultural transmission links between Europe and Argentina, based on a discursive construction based on the philia -one of the fundamental attitudes that govern the representation of the Other in intercultural dialogue. Carine Roitfeld, photographed by Mario Testino, was interpreted in the light of Daniel-Henri Pageaux’s theory, which placed the appreciation of the "culture looked" at the center of a permanent tension whose mirror reflects an explicitly duplicated "I-narrator" as a double body [white] of European high fashion. Vogue Paris establishes an ambiguous and inflamed intercultural dialogue, whether through "bubbling temperament", "fashion theater", "Latin excess" or "stunning pain" attributed to the image of Argentina and its own image.